PENANAMAN KARAKTER DISIPLIN MELALUI EKSTRAKURIKULER PENCAK SILAT DI SD MUHAMMADIYAH 11 SEMARANG - Lilik Novita Sari; Mei Fita Asri Untari; Asep Ardiyanto (JANACITTA, 2020)
Character education is one of the efforts to instill noble character values in order to become a better person. It can be seen that the cultivation of this noble character is the foundation of the nation's character. But in reality that the character of the present age is in a phase of concern. This can be seen in many problems which focus on the loss of sublime characters that are not well embedded. So that character planting needs to be done early on through family, school, community and government. One of them is through the planting attitude of habituation which is done in schools with good aims that are closely related to the character of discipline. Which can be embedded either through training activities, habituation through anything, for example with pencak silat extracurricular. Therefore, researchers try to analyze the characteristics of any discipline that is embedded in pencak silat extracurricular activities. Therefore, this study analyzes the characters found in pencak silat extracurricular activities with a focus on disciplinary characters at SD Muhammadiyah 11 Semarang. Where the character value has been instilled in by the teacher since the low class by requiring students to follow pencak silat extracurricular activities starting from class 3-5. Therefore, researchers use a qualitative approach. In this study using data collection techniques that are needed is by observation, interview and documentation. Based on the results of research that students have shown aspects of the character of discipline through pencak silat extracurricular activities and habituation in SD Muhammadiyah 11 Semarang.